Ossifying Renal Tumor of Infancy: Laparoscopic Treatment and Literature Review. (23rd October 2018) - Hajiran, Ali; Jessop, Morris; Werner, Zachary; Crigger, Chad; Barnard, John; Vos, Jeffrey; Ost, Michael
Abstract : We present an unusual case of a rare ossifying renal tumor of infancy. A 6-month-old male initially presented with gross hematuria and without any palpable abdominal mass. Renal ultrasound and MRI showed a right lower pole, calcified, endophytic renal mass. Laparoscopic radical nephrectomy was performed without complications. Pathology demonstrated an ossifying renal tumor of infancy. We report this case, in addition to a review of the literature for similar cases, to highlight a rare renal tumor in infancy that can be managed laparoscopically.